Laboratory of Senses - E. V. Abramovskikh (Tsentr nauchnykh i obrazovatelnykh proektov, 2017)
It is reported about a series of scientific and research events “Laboratory of Senses” organized in October and December 2016 at the Philological faculty of Samara State Socio-Pedagogical University. The content and purpose of “Laboratory of Senses” are characterized - teaching the analysis of literary text in literary, philological and linguistic methodology aspects with the achievements of various methodologies and scientific schools. Constructive performance of this series of activities carried out by teachers of the University with the bachelors and undergraduates is described.